2005
DOI: 10.1098/rspb.2004.2976
|View full text |Cite
|
Sign up to set email alerts
|

Among- and within-patch components of genetic diversity respond at different rates to habitat fragmentation: an empirical demonstration

Abstract: Habitat fragmentation is a ubiquitous by-product of human activities that can alter the genetic structure of natural populations, with potentially deleterious effects on population persistence and evolutionary potential. When habitat fragmentation results in the subdivision of a population, random genetic drift then leads to the erosion of genetic diversity from within the resulting subpopulations and greater genetic divergence among them. Theoretical and simulation analyses predict that these two main genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 48 publications
6
128
1
Order By: Relevance
“…Others studies also show correlation between genetic differentiation and contemporary landscape features, and between genetic diversity and historical factors (i.e. Keyghobadi et al, 2005a). Matrix resistance was the most important factor explaining variation in AR and genetic differentiation (AR and F ST , G ST ' and Jost' D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Others studies also show correlation between genetic differentiation and contemporary landscape features, and between genetic diversity and historical factors (i.e. Keyghobadi et al, 2005a). Matrix resistance was the most important factor explaining variation in AR and genetic differentiation (AR and F ST , G ST ' and Jost' D).…”
Section: Resultsmentioning
confidence: 99%
“…The different pattern in the effect of landscape features may be because of a higher temporal lag in genetic diversity and inbreeding in comparison with AR (Keyghobadi et al, 2005a). AR tends to respond faster than genetic diversity, because of the loss of rare alleles due to marked reduction in habitat (Young et al, 1996;Keyghobadi et al, 2005a).…”
Section: Genetic Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…1), has demonstrated that movement (7)(8)(9) and gene flow (10,11) are severely limited by encroaching forests. These butterflies are restricted to open alpine meadows in the Rocky Mountains where their larval host plant, lance-leaved stonecrop, Sedum lanceolatum, and adult nectar resources are present (12).…”
mentioning
confidence: 99%